Research on Real-Time Detail Enhancement Algorithm for Endoscopic Video Images and Hardware Implementation - Tianci Wu; Yu Pang; Yuanfa Wang; Wenpeng Su (IET Circuits, Devices and Systems)
In order to solve the problems of low contrast and weak detail information of endoscope images, the image adaptive histogram detail enhancement algorithm is presented. Although the adaptive histogram equalization (AHE) algorithm has been studied in some depth, the detail enhancement algorithm is relatively complicated and difficult to implement in endoscope hardware. In order to realize the real-time and adaptive enhancement of endoscope image details on the hardware system, the AHE algorithm is improved to reduce the hardware resource consumption and time complexity. The improved algorithm selects the segmentation condition suitable for real-time image, the threshold interception, and the pipeline structure to process the low contrast endoscopic image. Xilinx’s Artix-7 chip is used to implement the hardware circuit and process images with a resolution of 640 x 480 in real time at a rate of up to 160 frames per second. The design utilizes 25K look-up tables (LUTs), 6K flip–flops, and 33 block RAMS. The experimental results show that the improved algorithm has the characteristics of fast processing speed, good detail enhancement effect, and strong portability, which can meet the requirements of real-time video processing in endoscopy.